Food insecurity and lifestyle behaviours in university students amidst the COVID-19 pandemic: a comparative survey across three countries - Maria M. Witkowiak; Adama Nana Idris; Alma Sato; Hala Sacre; Chadia Haddad; Rana Rizk; Diana Malaeb; Jana Strahler; Pascale Salameh; Despo Ierodiakonou (BMC Public Health)
Abstract Background University students, often unemployed and reliant on low-nutrition foods, are susceptible to food insecurity (FI) with potential physical and mental health challenges. This study explores FI and its impact on lifestyle behaviours among university students. Methods A cross-sectional web-based study was performed by sending an online questionnaire to university students in Lebanon, Cyprus, and Germany during the COVID-19 pandemic. Using validated measures, i.e., the Household Food Insecurity Access Scale, International Physical Activity Questionnaire, Pittsburgh Sleep Quality Index, and Mediterranean Diet Adherence Screener, adjusted linear regression models were performed to assess the associations between country, FI and physical activity, sleep quality, and diet. Results In a convenience sample of 611 individuals (350 in Germany, 214 in Lebanon, and 47 in Cyprus) enrolled in the study, 547 provided complete response. 190 (34.7%) experienced FI, of whom 52 (9.5%) were severely food-insecure, with variation of FI prevalence between countries (18.9% in Germany, 14.9% in Cyprus, and 60.3% in Lebanon). Lifestyle behaviours also differed between participants from the three countries, with students in Germany exhibiting the highest physical activity level and the lowest adherence to the Mediterranean diet compared with Lebanon and Cyprus. On the other hand, participants from Lebanon and Cyprus had similar physical activity and diet behaviours. Concerning sleep, students in Cyprus showed the poorest quality. FI significantly correlated with reduced physical activity (beta − 0.171, 95% Confidence Interval (-0.313, -0.029)), but not with sleep or diet. The country of residence independently predicted lifestyle behaviours (p < 0.05). Conclusions This study suggests that FI impacts university students in countries of varying income levels, and the country of residence independently influences lifestyle behaviours. Larger-size studies are essential to confirm these findings and further explore FI’s impact on university students outside the context of the pandemic.